Treatment of a long-acting anticoagulant rodenticide poisoning cohort with vitamin K1 during the maintenance period. Issue 51 (December 2016) - Long, Jianhai; Peng, Xiaobo; Luo, Yuan; Sun, Yawei; Lin, Guodong; Wang, Yongan; Qiu, Zewu
Abstract : Abstract: Currently, there are few guidelines for the use of vitamin K1 in the maintenance treatment of long-acting anticoagulant rodenticide (LAAR) poisonings. We explored factors in the treatment of LAAR poisoning during the maintenance period in order to suggest feasible treatment models. Data from 24 cases of anticoagulant rodenticide poisoning in our hospital were collected from January 2013 to May 2016. The patients' sex, age, coagulation function, total time from poisoning to treatment with vitamin K1 (prehospital time), vitamin K1 sustained treatment time (VKSTT), anticoagulant rodenticide category, and specific poison dosage were collected. Multivariate analysis was used to evaluate the correlation between vitamin K1 dosage and other factors during the maintenance period. Only VKSTT (partial regression coefficient −1.133, 0.59, P = 0.035) had an obvious influence on the therapeutic dose of vitamin K1 required during the maintenance period. After an initial pulse therapy, the bleeding and coagulation functions were stabilized, and the patients were subsequently treated with vitamin K1 during the maintenance period. Over time, the maintenance dose of vitamin K1 (10–120 mg/d, intravenous drip) was gradually decreased and was not related to toxicant concentration. Abstract : Supplemental Digital Content is available in the text